Pengaruh Penerapan Model Problem Based Learning (PBL) terhadap Pemahaman Konsep Matematika Siswa - Fadlia M. Jafar; Lisnasari Andi Mattoliang (Alauddin Journal of Mathematics Education, 2025)
Conceptual understanding is an important aspect in mathematics learning because it is the basis for students to learn the next material. This study aims to analyze the effect of the application of the Problem Based Learning (PBL) model on the mathematical concept understanding of grade VII students of SMPN 40 Makassar. The study used a quantitative approach with a quasi-experimental design of the nonequivalent control group type, involving class VII.2 as the experimental class and VII.3 as the control class. Data were collected through pretests and posttests, then analyzed using descriptive statistics and t-tests. The results showed that the average conceptual understanding score in the PBL class was 78, higher than the control class which obtained an average of 62. The t-test produced , namely , so there was a significant difference between the two groups. This finding indicates that the application of PBL contributes to improving students' mathematical concept understanding. The implications of this study confirm that the PBL model can be used as an alternative learning model to support deeper conceptual mastery in the classroom in mathematics learning.